The origins of agriculture: Intentions and consequences. (January 2021) - Jones, Glynis; Kluyver, Thomas; Preece, Catherine; Swarbrick, Jennifer; Forster, Emily; Wallace, Michael; Charles, Michael; Rees, Mark; Osborne, Colin P.
Abstract: We synthesise the results of a large programme of plant ecological research to investigate the selective pressures driving crop domestication and the origins of agriculture in western Asia. We explore this primarily through a series of experiments, comparing the ecological characteristics of: (1) domesticated cereal and pulse species with their wild progenitors and (2) the wild progenitor species with other west Asian grasses and legumes that did not become domesticated during the emergence of agriculture. In particular, we consider the balance between deliberate human selection and unintended consequences of human actions in driving the domestication process. Taken together, our results provide the first empirical evidence to suggest that ecological processes, and unintended selection due to competition between growing plants within anthropogenic environments, may have played a more significant part in the emergence of agriculture than previously supposed. Such human-plant co-evolutionary mechanisms would render unnecessary the search for 'push' or 'pull' factors, dependent on deliberate human invention to solve a problem or to satisfy a need, as prime movers to explain why hunter-gatherers switched to an agricultural way of life. Highlights: Southwest Asian crop progenitors did not have greater total seed yield than other wild species. Seed enlargement in vegetable crops due to domestication was comparable with that of grain crops. Southwest Asian crop progenitors germinate faster & have larger seedlings than other wild species. Domestication potentially driven by competition between plants in anthropogenic environments. Suggests a significant role for co-evolution & unintended selection in the origins of agriculture.